Mechanisms and recent advances in the diagnosis and treatment of nitrous oxide-induced peripheral neuropathy: a narrative review - Zou, Xiaodi; Yi, Fangyu; Zhou, Weijie; Dong, Yanzhao; Alhaskawi, Ahmad; Zhou, Haiying; Ezzi, Sohaib Hasan Abdullah; Kota, Vishnu Goutham; Abdulla, Mohamed Hasan Abdulla Hasan; Alenikova, Olga; Abdalbary, Sahar Ahmed; Lu, Hui; et al. (Frontiers in Neurology, 2024)
Under standard conditions, nitrous oxide (N2O) manifests as a colorless, odorless gas with a mildly sweet taste. The compound finds applications in various fields, including its use as an aerosol propellants, an accelerant in motor racing, and an anesthetic in surgical procedures and dentistry. Unfortunately, the recreational misuse of N2O has become prevalent among young individuals due to its euphoric and hallucinogenic effects. Compounding this issue is the fact that nitrous oxide can be easily obtained from over-the-counter household items, facilitating its non-medical use. The global community has witnessed a surge in the recreational utilization of nitrous oxide gas in recent years. Despite the widespread non-medical abuse of N2O, there remains inadequate understanding of the potential adverse effects resulting from exposure to it. This paper provides an overview of management findings, laboratory and electrodiagnostic characteristics, as well as clinical presentations associated with neurological disorders induced by nitrous oxide usage.